The Role of employee satisfaction in enhancing employee’ performance– An empirical study on a sample of pharmacies of the state of Khenchela (Algeria) - Adjali, Dalal (Journal of Human Sciences, 2017)
The aim of this study is to empirically examine the employee satisfaction and its relationship with the enhancing of employee performance in Algerian pharmacies. We found that: “employee satisfaction” is positively associated with “employee performance” in Algerian pharmacies. There is a statistically significant difference amongst the employees in Algerian pharmacies due to privacy determinants (gender, experience, and education level).